8.18 STRUCTURAL FEATURES IN DAZAI OSAMU’S NOVEL "LOST" - Mamurjonova G.R. (teacher) Tursunova N.T. (senior teacher) at the Department of Japanese philology TSUOS (Innovative technologies in construction Scientific Journal, 2024)
This article examines the compositional features of the novel "Lost" by the Japanese modernist writer Dazai Osamu. Dazai Osamu is one of the greatest writers of the 20th century. His work cannot be attributed to any particular genre. Many call him a classic of the "novel about himself" ("watakushi-shosetsu"), others talk about his closeness to romanticism, but despite the fact that both are undoubtedly present in his work, Osamu Dazai’s prose is difficult to fit into narrow frames one genre. "Lost" is one of the stories of Dazai Osamu. Social movements and political development of the country occupy an important place here. The author is sure that war is a real absurdity, which brings nothing but destruction. He is sickened by the inhumanity of society, which is clearly manifested in the main character. Keywords: XX century, the story "The Lost", "existentialism", Dazai Osamu, "Oba Yozo" magazine "Bungeyishunju" ("Literary chronicle") The work of Dazai Osamu (Tsushima Shuji, 1909-1948) reflected the self-alienation of the individual with his moods of self-destruction and fatigue. The author, as a prominent representative of the "Non-Entertaining group" ("Shingesakuha"), expressed his pessimistic worldview in his last work "No longer a man" ("Ningen shikkaku", 1948), in which he showed the state of decline of man and society. In this work it is impossible not to see the imprint of Z.’s psychoanalysis. Freud, the literature of D. G. Lawrence, the philosophy of existentialism . An outstanding master of words, Dazai reflected in his works of art the tragedy of his era, the throwing of the intelligentsia, and his own mental suffering. Dazai’s last major work was the novel "No Longer a Man", in which a hero named Oba Yozo tells a story about his bitter fate. The story is considered autobiographical, since its events converge with the facts of the writer’s life, however, literarily reinterpreted, they bring out a portrait of the generation to which the author belonged.